RELATIONSHIP BETWEEN SPIRITUAL WELL-BEING AND QUALITY OF LIFE OF UNIVERSITY X STUDENTS DURING COVID-19 - Heng, Pamela Hendra; Lathiifah, Septi; Hutabarat, Franklin (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2021)
During the COVID-19 pandemic, many daily activities are carried out from home. Likewise, educational activities are carried out at home online. This reduces physical activity and can lead to decrease physical and spiritual health. The purpose of this study was to determine the relationship between spiritual well-being and quality of life in university students during the COVID-19 pandemic. Participants in this study consisted of 54 men and women with an age range of 19 years to 22 years. This research is non-experimental quantitative research with a sampling technique using purposive sampling. The measuring instrument used to measure spiritual well-being is the spiritual well-being questionnaire (SWQ) compiled by Gomez and Fisher and the measuring instrument for measuring the quality of life uses the Indonesian version of the WHOQOL-BREF measuring instrument, which was developed by Purba et al. The results showed that there was a positive relationship between spiritual well-being and quality of life in students during the COVID-19 pandemic (p= 0.000 < 0.05), the higher the spiritual well-being of students, the higher the quality of life of students. Additional data analysis was carried out to look for different tests, based on the results of the study there were differences in quality of life-based on gender.